The European Cultural Tradition in the Wolfenbüttel Postil (1573/1574) - Gelumbeckaitė, Jolanta (Vilnius University Open Series, 2018)
[full article and abstract in Lithuanian; abstracts in English and German] The so-called Wolfenbüttel Postil (1573/1574) – an anonymously handwritten Lithuanian Lutheran work, which originated in the period between 1565 and 1573 – is a compilation based on at least ten Latin postils. This codex, consisting of sermons dedicated to an entire liturgic year, is the oldest Lithuanian coherent text which is not restricted only to the translations of a canonical text. Furthermore, it is one of the most extensive texts in the early modern history of Lithuanian. The Postil testifies the dissemination of Reformation writings and ideas in the Lithuanian language area and represents a florilegium of European homiletic tradition. It includes considerable parts of an originally written text and of hardly verifiable compilations. Methodologically, the translation is typical for the 16th century. Literally translated excerpts are followed by originally written parts, or translations from other sources are included. The Lithuanian translation is selective and paradigmatic. The text is supplemented with exempla fidei, quotations, allusions and paraphrases. The Wolfenbüttel Postil thus offers an anthological reception of numerous classics, church fathers, medieval theologians and various medieval and early modern historians: Strabo, Cicero, Pliny the Elder, Pliny the Younger, the Disticha Catonis; Athanasius, (pseudo-)Augustine, (pseudo-) Jerome, Gregory of Nazianzus, John Chrysostom, Josephus Flavius, Eusebius of Caesarea, (pseudo-)Hegesippus, (pseudo-)Basil the Great, Rufinus of Aquileia, Sulpicius Severus, Cassiodorus, Vigilius of Thapsus, Leo the Great, Fulgentius of Ruspe, Gregory the Great, Isidore of Seville, (pseudo-)Bernard of Clairvaux; Paulus Diaconus, Dietrich of Apolda and Pomponius Laetus (Giulio Sanseverino). A large part of the European cultural tradition could have reached the Lithuanian-speaking audience through this Postil for the very first time. Die europäische Kulturtradition in der Wolfenbütteler Postille (1573/1574) Die sogenannte Wolfenbütteler Postille von 1573/1574 ist das erste ausführliche handschriftliche Textzeugnis der litauischen Schriftsprache und einer der umfangreichsten litauischen Texte des gesamten 16. Jahrhunderts. Diese im Herzogtum Preußen entstandene lutherische Predigtsammlung gilt damit als eine der wichtigsten Quellen zur litauischen Sprach-, Kirchen- und Kulturgeschichte. Der litauische Text ist ein aussagekräftiges Dokument im Hinblick auf die Verbreitung der Reformationsschriften und des reformatorischen Gedankengutes im litauischsprachigen Milieu. Die Postille bildet ein Florileg europäischer homiletischer Tradition, die dem litauischen Kulturkreis durch das Predigen in litauischer Sprache zum ersten Mal zugänglich gemacht wurde. In dieser Hinsicht ist sie eine unikale Zusammenstellung reformatorischer Lehre. Die WP ist eine vielschichtige Übersetzung und Bearbeitung. Die vergleichende Analyse des litauischen Textes mit den Vorlagentexten weist auf eine eindeutige Übersetzungsrichtung Latein– Litauisch hin. Die Übersetzungstrategien sind typisch für die Frühe Neuzeit. Die Textübertragung ist nicht immer adäquat, der Vorlagentext wird bisweilen zielorientiert bearbeitet, kommentiert, ergänzt, verkürzt und paraphrasiert. Die Übersetzung ist oft um exempla fidei, Zitate und Anspielungen ergänzt. Die Postille bietet somit eine anthologische Rezeption von zahlreichen Klassikern, Kirchenvätern, mittelalterlichen Theologen und verschiedenen mittelalterlichen sowie frühneuzeitlichen Historikern. Zitiert werden Strabon, Cicero, Plinius d. Ä ., Plinius d. J. und die vermutlich im 3. Jahrhundert nach Chr. entstandenen Disticha Catonis; Athanasius, (Pseudo-)Augustinus, (Pseudo-)Hieronymus, Gregor von Nazianz, Johannes Chrysostomus, Josephus Flavius, Eusebius von Caesarea, (Pseudo-)Hegesippus, (Pseudo-)Basilius der Große, Rufin von Aquileia, Sulpicius Severus, Cassiodorus, Vigilius von Thapsus, Leo der Große, Fulgentius von Ruspe, Gregor der Große, Isidor von Sevilla und (Pseudo-)Bernhard von Clairvaux; Paulus Diaconus, Dietrich von Apolda und Pomponius Laetus (Giulio Sanseverino). Wie in der Frühneuzeit üblich, sind die Quellen der Zitate nicht immer angegeben und die Zitate selbst oft paraphrasiert. Die in der WP vorkommenden Zitate stellen die ersten schriftlichen Übersetzungen ins Litauische dar.